Audiovisual temporal adaptation of speech: temporal order versus simultaneity judgments. - Vatakis, A; Navarra, J; Soto-Faraco, S; Spence, C (2008)
The temporal perception of simple auditory and visual stimuli can be modulated by exposure to asynchronous audiovisual speech. For instance, research using the temporal order judgment (TOJ) task has shown that exposure to temporally misaligned audiovisual speech signals can induce temporal adaptation that will influence the TOJs of other (simpler) audiovisual events (Navarra et al. (2005) Cognit Brain Res 25:499-507). Given that TOJ and simultaneity judgment (SJ) tasks appear to reflect different underlying mechanisms, we investigated whether adaptation to asynchronous speech inputs would also influence SJ task performance. Participants judged whether a light flash and a noise burst, presented at varying stimulus onset asynchronies, were simultaneous or not, or else they discriminated which of the two sensory events appeared to have occurred first. While performing these tasks, participants monitored a continuous speech stream for target words that were either presented in synchrony, or with the audio channel lagging 300 ms behind the video channel. We found that the sensitivity of participant's TOJ and SJ responses was reduced when the background speech stream was desynchronized. A significant modulation of the point of subjective simultaneity (PSS) was also observed in the SJ task but, interestingly, not in the TOJ task, thus supporting previous claims that TOJ and SJ tasks may tap somewhat different aspects of temporal perception.